The Logic of the Heart: Ebner and Tischner - Miłosz Hołda (Nicolaus Copernicus University in Toruń, 2017)
In this article I propose a reflection on "the logic of the heart" in the thought of Ferdinand Ebner and Józef Tischner. "Logic" I understand as an order or clearly designated criteria that must be followed. It is a synonym of the mind, which works according to some specific rules. "Heart" is synonymous with the sphere of intuition, which allows one to examine truths to which the mind itself has no access. Speaking of "the logic of the heart" is an expression of the understanding of the human being, which on the one hand is not confined to the mind, but on the other hand treats his intuition as an area that can function properly only according to the order. I reconstruct the understanding of "the logic of the heart" by Ebner and Tischner. I think that such reconstruction is very useful because "the logic of the heart" not only has a lasting philosophical value, but it is precisely what we need today to solve philosophical and non-philosophical problems.